Intestinal immune-potentiation by a purified alkylglycerols compound - Kantah, M.K.; Wakasugi, H.; Kumari, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Alkylglycerols have shown immune stimulant and adjuvant activity in several studies and the aim of the present research was to assess in particular the effect of shark liver-derived alkylglycerols on gut immune system. C57BL/6 mice, fed under specific pathogen free conditions, were randomly divided into two groups: a) fed normal laboratory food or b) added with alkylglycerols (2 mg/day/mouse) for 3 weeks. Intraepithelial lymphocytes (IEL) were retrieved from the small intestine and tested for NK and tumor cytotoxicity. Lymphocytes from liver, spleen and IEL were also assessed as for their counting and phenotypic characterization. Under supplementation with alkylglycerols, the number of lymphocytes yielded by the small intestine increased by to almost 40%. Moreover, the ratio of CD8αβ+TCRαβ+ cells/CD8αα+TCRαβ+ cells remarkably increased. In parallel with this reshaping in the distribution of lymphocyte subsets, tumor cytotoxicity of IEL against P815 cells and cytokine production from circulating lymphocytes were also enhanced. These data show that phylogenetically developed lymphocytes (CD8αβ+, TCRαβ+) were significantly activated by the oral administration of alkylglycerols. The present results indicate that purified alkylglycerols might have such significant potential via the enhancement of intestinal immunity, especially in the small intestine.